The benefits and perspectives of the palm oil industry in Malaysia - Lai V.; Yusoff N.Y.M.; Ahmed A.N.; Huang Y.F.; Boo K.B.W.; El-Shafie A. (Springer Science and Business Media B.V., 2025)
Palm oil plantations have rapidly developed over the past five decades in nations with tropical climates due to high demand for the product. Malaysia?s position as the world?s second largest producer and exporter of palm oil after Indonesia attests to the economic importance of palm oil to the country. This article aims to provide a comprehensive review of the Malaysian palm oil industry, highlighting its potential applications in various fields of study. The concluding section identifies inadequacies in the industry that could be addressed through the adoption and integration of Fourth Industrial Revolution technologies such as big data analysis and Artificial Intelligence, which would promote a more sustainable palm oil industry. ? The Author(s), under exclusive licence to Springer Nature B.V. 2024.